Familial Adenomatous Polyposis: An Uncommon Autosomal Genetic Condition - Simran Khan; Shreya Giri; Suhit Naseri (Journal of Clinical and Diagnostic Research)
A 40-year-old man presented to the Department of Emergency Medicine with severe pain in abdomen which was present for the past two days. He experienced three episodes of vomiting and two episodes of diarrhoea which was greenish in colour without any blood or mucus. A mass from the anal region was also noticed while defecating which was insidious in onset and gradually progressing in size since one month. Physical examination upon deep palpation revealed generalised abdominal pain but no signs of peritoneal involvement. He claimed to have lost weight during the last four months. Notably, his family history included several relatives who had intestinal polyps and colon cancer. Laboratory findings indicated 8.5 g/dL haemoglobin levels and a mean corpuscular volume of 70 fL, along with a positive faecal occult blood test. Normal serum levels of electrolytes, creatinine, glucose, haemoglobin, and pH were observed. A differential diagnosis of haemorrhoids and rectal ulcers was made.